2008
DOI: 10.1097/scs.0b013e318163e415
|View full text |Cite
|
Sign up to set email alerts
|

Bone Generation in the Reconstruction of a Critical Size Calvarial Defect in an Experimental Model

Abstract: This study was designed to investigate the optimal combination of known osteogenic biomaterials with shape conforming struts to achieve calvarial vault reconstruction, using a canine model. Eighteen adolescent beagles were divided equally into 6 groups. A critical-size defect of 6 x 2 cm traversed the sagittal suture. The biomaterials used for calvarial reconstruction were demineralized perforated bone matrix (DBM), recombinant human bone morphogenetic protein 2 (rhBMP2), and autogenous platelet-rich plasma (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
30
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 37 publications
2
30
1
1
Order By: Relevance
“…The trabecular nature of rhBMP-2-generated bone has been documented previously. 7,8,14 This gross disorganization resulted in variability across treatment groups with regard to the compactness of the newly formed bone. When compared side by side under identical magnification, groups B and C showed trabecular bone growth, with group C qualitatively superior Volume 127, Number 5 • Regeneration of Large Cranial Defects to group B.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The trabecular nature of rhBMP-2-generated bone has been documented previously. 7,8,14 This gross disorganization resulted in variability across treatment groups with regard to the compactness of the newly formed bone. When compared side by side under identical magnification, groups B and C showed trabecular bone growth, with group C qualitatively superior Volume 127, Number 5 • Regeneration of Large Cranial Defects to group B.…”
Section: Discussionmentioning
confidence: 97%
“…Several experimental models have investigated how bone morphogenetic protein therapies can be safely expanded to address bony defects throughout the skeleton, including the calvaria. [7][8][9][10] Although the successful application of rhBMP-2 therapy to the calvaria would potentially obviate the need for autogenous tissue harvest, the unwanted effects of rhBMP-2 therapy must first be minimized before it can be considered a preferred therapy. The development of seromas and the formation of ectopic bone following rhBMP-2 treatment has been described previously.…”
mentioning
confidence: 99%
“…[24][25][26][27][28] Although all concentrations of rhBMP-2 appeared to enhance bone formation on the perisoteal surface of the suture, the suture was fused with excessive bone formation, once exceeding the threshold of 0.1 mg/mL of rhBMP-2. If this threshold was not met, rhBMP-2 stimulated bone formation at the edges adjacent to the expanding suture.…”
Section: Discussionmentioning
confidence: 92%
“…On the contrary, some investigators have demonstrated no benefit or even a negative effect on bone regeneration with PRP. 23,24 It remains questionable whether or not the PRP can enhance new bone formation. In our study, the suture width was consistently less in the PRP gel group than in the control group, as shown on histological slices and micro-CT images (Figs.…”
Section: Discussionmentioning
confidence: 99%